Distinct Roles of Mus81, Yen1, Slx1-Slx4, and Rad1 Nucleases in the Repair of Replication-Born Double-Strand Breaks by Sister Chromatid Exchange - Muñoz-Galván, Sandra (American Society for Microbiology, 2012)
Most spontaneous DNA double-strand breaks (DSBs) arise during replication and are repaired by homologous recombination (HR) with the sister chromatid. Many proteins participate in HR, but it is often difficult to determine their in vivo functions due to the existence of alternative pathways. Here we take advantage of an in vivo assay to assess repair of a specific replication-born DSB by sister chromatid recombination (SCR). We analyzed the functional relevance of four structure-selective endonucleases (SSEs), Yen1, Mus81-Mms4, Slx1-Slx4, and Rad1, on SCR in Saccharomyces cerevisiae. Physical and genetic analyses showed that ablation of any of these SSEs leads to a specific SCR decrease that is not observed in general HR. Our work suggests that Yen1, Mus81-Mms4, Slx4, and Rad1, but not Slx1, function independently in the cleavage of intercrossed DNA structures to reconstitute broken replication forks via HR with the sister chromatid. These unique effects, which have not been detected in other studies unless double mutant combinations were used, indicate the formation of distinct alternatives for the repair of replication-born DSBs that require specific SSEs.